The Pengaruh Specific Surface dari Tulangan Galvanised Welded Wire-Mesh terhadap Daktilitas Displasemen Panel Ferrocement - I Nyoman Merdana; Fathmah Mahmud; I Dewa Gede Jaya Negara; I Wayan Suteja; Nengah Erna Purnama Devi; Nazula Muthia Sahlani (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2026)
For building construction located in high-risk seismic zone, ductile material is required which can be fulfilled with Ferrocement. Ferrocement has been widely applied as construction material and strengthening damaged structures due to its unique properties. In this study, the effect of Specific surface of wire-mesh reinforcement on the Displacement ductility behaviour of Ferrocement panels was investigated. Ferrocement panels of 20x200x600mm, made of 1Pc:3Ps mortar and water-cement ratio of 0.50, was prepared. The Ferrocement panels were reinforced with evenly distributed Galvanised welded wire-mesh having various opening sizes and wire-mesh diameter. The main variable in this research is the Specific surface. Ferrocement panels were tested with third-point loading correspond to SNI 4431:2011. Based on data analysis it was concluded that Displacement ductility raised as the Specific surface Sr increase. Furthermore, minimum specific surface of 4mm2/mm3 is recommended for seismicity zone